2004
DOI: 10.1073/pnas.0404110101
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis AtRAD51 gene is dispensable for vegetative development but required for meiosis

Abstract: The maintenance of genome integrity and the generation of biological diversity are important biological processes, and both involve homologous recombination. In yeast and animals, homologous recombination requires the function of the RAD51 recombinase. In vertebrates, RAD51 seems to have acquired additional functions in the maintenance of genome integrity, and rad51 mutations cause lethality, but it is not clear how widely these functions are conserved among eukaryotes. We report here a loss-of-function mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
331
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(348 citation statements)
references
References 59 publications
16
331
1
Order By: Relevance
“…Among these mutants, atrad50, atmre11, atrad51, atrad51c, and atxrcc3, which have defects in the repairing of AtSPO11-induced DSB, exhibited similar meiotic chromosome behaviors like asynaptic homologs and/or chromosome fragmentation (Bleuyard et al, 2004a;Bleuyard and White, 2004;Li et al, 2004Li et al, , 2005Puizina et al, 2004). The meiotic chromosome fragmentation could be suppressed by mutation in AtSPO11-1 (Bleuyard et al, 2004b;Li et al, 2004Li et al, , 2005Puizina et al, 2004), which provides a direct evidence that the origin of the DNA breaks in these mutants is the unrepaired DSBs generated by AtSPO11. However, the atspo11-1 mutation only partially rescues meiotic chromosome fragmentation in atspo11-1/atatr, atspo11-1/ atatm double mutants and the atspo11-1/atatr/atatm triple mutant (Culligan and Britt, 2008).…”
Section: Distinctive Chromosome Behavior Of Osrpa1a Mutants and The Omentioning
confidence: 80%
“…Among these mutants, atrad50, atmre11, atrad51, atrad51c, and atxrcc3, which have defects in the repairing of AtSPO11-induced DSB, exhibited similar meiotic chromosome behaviors like asynaptic homologs and/or chromosome fragmentation (Bleuyard et al, 2004a;Bleuyard and White, 2004;Li et al, 2004Li et al, , 2005Puizina et al, 2004). The meiotic chromosome fragmentation could be suppressed by mutation in AtSPO11-1 (Bleuyard et al, 2004b;Li et al, 2004Li et al, , 2005Puizina et al, 2004), which provides a direct evidence that the origin of the DNA breaks in these mutants is the unrepaired DSBs generated by AtSPO11. However, the atspo11-1 mutation only partially rescues meiotic chromosome fragmentation in atspo11-1/atatr, atspo11-1/ atatm double mutants and the atspo11-1/atatr/atatm triple mutant (Culligan and Britt, 2008).…”
Section: Distinctive Chromosome Behavior Of Osrpa1a Mutants and The Omentioning
confidence: 80%
“…T‐DNA insertion line cycb1;3 (pst15850) was obtained from the RIKEN collection (Yokohama, Japan) and cycb1;4 from the GABI‐KAT collection (Bielefeld, Germany) (Kleinboelting et al , 2012). The ku70 (Riha et al , 2002), wee1 (De Schutter et al , 2007), and rad51 (Li et al , 2004) mutants were described previously. The reporter line uidA/IC9C was used as described in Molinier et al (2004) and the pCDKB1;1:GUS line as in Boudolf et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous results suggested that AtRad51C and AtXrcc3 act together and are involved in DNA repair and meiotic recombination. Recently, AtXRCC3 and AtRAD51 knockout mutants have been identified and characterized in Arabidopsis Li et al, 2004). atrad51 and atxrcc3 mutants developed normally in vegetative stage but showed male and female sterility, due to chromosome fragmentation after pachytene in both types of gametogenesis.…”
mentioning
confidence: 99%